ANALISIS DAN PERANCANGAN SISTEM INFORMASI AKUNTANSI PENDAPATAN PADA ATLAS SPORTS CLUB (STUDI KASUS: PERUS-AHAAN KEBUGARAN) - Jonaidy, Hikmah; Wehartaty, Tineke; Natalia, Irene (Widya Mandala Surabaya Catholic University, 2012)
Revenue is a very important process as a source of revenue for the company and is a determining factor in view of the profits of the company. Therefore, any company especially a company engaged in the service sector, which requires income information systems in accordance with company requirements. Internal controls over revenue will go well and produces good quality information, if the company had revenues of information systems that can support the company’s operational activities, thus the effectiveness and efficiency of the company can be reached. Therefore, researchers are trying to do research on Atlas Sports Club revenue infor-mation system, company that is engaged in fitness. The purpose of this research is to provide advice and input on the issues of the company, through the design of an integrated revenue information systems, so as to improve the effectiveness, efficiency and in-ternal control within the company. The type of research that is done is a case study, using qualitative data. The revenue infor-mation systems design include the design concept consists of system flowchart, data flow diagram (DFD), entity relationship dia-grams, and physical design consisting of the design of access, database, input and output that generates an application program revenue. The results of this study indicate that the presence of information system design revenue, the more access restrictions can be optimized, more adequate segregation of duties, the can provide satisfactory services to the customers, and reports can be generated to more accurately, relevant and timely.